Characterization of patients using insulin in a pharmacotherapeutic service and identification of hospital readmissions - Jessica S. Malta; Josiane M. Costa; Carla J. Machado; Maria A. Martins (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Objective: To characterize patients with insulin-dependent Diabetes Mellitus (DM) accompanied by a PF service in a teaching hospital, as well as to identify the occurrence of hospital readmissions and associated factors. Methods: This is a cross-sectional study carried out in a general teaching hospital, being included patients above 18 years old, of both genders, with type 1 or 2 DM diagnosis were admitted from April 2015 to April 2016, accompanied by the Pharmaceutical Follow-up Service of the hospital, who used insulin during hospitalization and received indication for using this drug in the hospital discharge prescription. Data were collected through consultation in electronic medical records and telephone contact after the hospital discharge. Data were recorded in a Microsoft Excel spreadsheet, with the patients subdivided into groups with and without readmission, followed by univariate analysis of associated factors by means of proportion comparison and logistic model with penalized likelihood. Results: Patients who were re-admitted had higher blood sugar values, fewer pharmaceutical interventions regarding insulin use, and longer average hospitalization time. The analysis of the association between variables and readmission did not present statistical significance. Conclusions: The study points out to weaknesses related to the offer of care to the patients under study, such as weaknesses in the coverage for offering actions related to health education in the periods before and after hospital discharge, difficulty in accessing the specialist physician and non-achievement of blood sugar measurement by some patients. There was no association between any of the analyzed variables and hospital readmission.